2014
DOI: 10.1123/japa.2012-0132
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscle Strengthening’s Improvement of Balance Performance in Community-Dwelling Older Adults: A Pilot Study

Abstract: To determine the effect of core muscle strengthening on balance in community-dwelling older adults, 24 healthy men and women between 65 and 85 years old were randomized to either exercise (EX; n = 12) or control (CON; n = 12) groups. The exercise group performed a core strengthening home exercise program thrice weekly for 6 wk. Core muscle (curl-up test), functional reach (FR) and Star Excursion Balance Test (SEBT) were assessed at baseline and follow-up. There were no group differences at baseline. At follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 22 publications
7
52
0
4
Order By: Relevance
“…This could be of importance in fall prevention in seniors since aging-induced balance deterioration appears to be more pronounced in a bilateral asymmetric stance in which m-l body sway is particularly evident (Amiridis, Hatzitaki, & Arabatzi, 2003;Onambele, Narici, & Maganaris, 2006). Several studies also reported gains in single-task balance ability in older individuals following core strengthening (Kahle & Tevald, 2014) and core instability training programs (Granacher, Lacroix, Muehlbauer, Roettger, & Gollhofer, 2012). The fact that the Pilates group did not significantly improve postural control in the single-task was somewhat surprising, considering the results of previous Pilates training studies in older women (Barker et al, 2015;Bullo et al, 2015;Newell, Shead, & Sloane, 2012;Pata, Lord, & Lamb, 2014;Siqueira Rodrigues, Ali Cader, Bento Torres, Oliveira, & Martin Dantas, 2010).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This could be of importance in fall prevention in seniors since aging-induced balance deterioration appears to be more pronounced in a bilateral asymmetric stance in which m-l body sway is particularly evident (Amiridis, Hatzitaki, & Arabatzi, 2003;Onambele, Narici, & Maganaris, 2006). Several studies also reported gains in single-task balance ability in older individuals following core strengthening (Kahle & Tevald, 2014) and core instability training programs (Granacher, Lacroix, Muehlbauer, Roettger, & Gollhofer, 2012). The fact that the Pilates group did not significantly improve postural control in the single-task was somewhat surprising, considering the results of previous Pilates training studies in older women (Barker et al, 2015;Bullo et al, 2015;Newell, Shead, & Sloane, 2012;Pata, Lord, & Lamb, 2014;Siqueira Rodrigues, Ali Cader, Bento Torres, Oliveira, & Martin Dantas, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Petrofsky et al (2005) showed that 4-week core strength training program increased strength of trunk flexors and extensors of seniors by 33-36%. Kahle and Tevald (2014) recently reported 44% increase in abdominal muscle endurance following core strengthening program in healthy older men and women. The authors also reported that changes in abdominal muscle endurance correlated significantly with the changes in the field balance tests (r = 0.44-0.61).…”
Section: Measurementioning
confidence: 98%
“…The performance of many of these systems declines with age, resulting in diminished balance and an increase in falls [4]. Kahle and Tevald [27] investigated the effect of core muscle strengthening on balance in community dwelling older adults, dividing 24 healthy men and women into two groups: one an exercise group who performed a core strengthening exercise programme at home three times a week for 6 weeks and one a control group. Participants in the exercise group performed a progressive programme consisting of eight exercises designed VOLUME 12 | ISSUE 1 | 2017 | 451 to increase the strength and endurance of the muscles of the core.…”
Section: Influence Of Physical Activity On Balancementioning
confidence: 99%
“…Patil et al (2014) state that, as a result of the study they carried out with 60 young swimmers with a mean age of 14,2±1,49, 6 weeks of core exercises have effect on 50 m free style swimming (p<0,05). In the literature, effects of core exercises on performance are a topic which has been scarcely studied on (Hibbs et al, 2008;Martens et al, 2011;Patil et al, 2014). However, for other branches there are various studies carried out.…”
Section: Resultsmentioning
confidence: 99%